The Potency of UB Forest Chitinolytic Bacteria to Promote Plant Growth and Inhibit Damping off Disease on Soybean - Roekhan, Achmad; Dayanti, Ayu Ike; Oktaviani, Rahmania; Dewi, Fibrianti Shinta; Anastasya, Nabilla Alya; Aini, Luqman Qurata (Research Journal of Life Science, 2021)
Damping off disease in soybean plants is caused by the fungal Rhizoctonia solani. The damping off disease causes a yield loss of up to 85-100%. The purpose of this study was determining the ability chitinolytic bacteria consortium of UB Forest's in suppressing damping off disease in vitro and in vivo as well as its potential to stimulate the growth of soybean plants. The research stages included isolation of the pathogenic fungus R. solani and the pathogenicity test. Rejuvenation chitinolytic bacterial isolates of UB Forest, test chitinolytic bacteria antagonist of UB Forest against R. solani fungus, test of Plant Growth Promoting (PGP) activities, synergy test of selected chitinolytic bacterial isolates, in vitro test for the inhibition of chitinase crude extract against R. solani, and inhibition test of chitinolytic bacteria consortium against damping off disease. The selected chitinolytic bacteria were code bacteria UB12, UB19, and UB52 with plant growth promoting activities with inhibition percentage of the pathogen R. solani of 73.9%, 67.4%, and 71.7%. The best chitinolytic bacterial isolates were the genus Bacillus sp. and Pseudomonas sp. The inhibition test of chitinase crude extract showed an inhibition percentage of 25-55%.